TAXATION ANALYSIS OF EDUCATIONAL FOUNDATIONS IN INDONESIA - Radhi Abdul Halim Rachmat; Hafied Noor Bagja; Yoga Tantular Rachman (SEAN Institute, 2023)
Education is an important industry in any country. The government, through its authority, provides ideal support by contributing a share of the budget as well as tax breaks. This study aims to provide an overview of how the Education Foundation's tax obligations, both income tax obligations and value added tax obligations, and tax facilities provided by the government to the Education Foundation, so that the Education Foundation's actors can fulfill tax obligations in accordance with applicable regulations and optimize the facilities provided to the Education Foundation.